A Case Study on Characterization and Management of Solid Waste at Selected Spiritual Sites in Dehradun, India - Vishal Kamboj; Purnima Devi; Ishrat Jaan; Ram Bhushan Prasad Singh; Aditi Bisht (AgroEnvironmental Sustainability)
The objective of this study is to evaluate the nature and extent of solid waste generated in selected areas of Dehradun, examining the disposal techniques employed and characterizing the waste produced during both normal days and festival days. Additionally, the study aims to educate the community on solid waste management practices and to calculate the average per capita waste generation. The results demonstrate that the ratio of biodegradable waste, primarily comprising flowers, fruits, and vegetables, constituted the highest proportion of waste in all analyzed temples. Of these, flowers represented the most prevalent form of biodegradable waste. The high percentage of floral waste indicates a significant volume of offerings, underscoring the necessity for the development of effective composting and organic recycling plans. Furthermore, the study demonstrates a correlation between an increase in the average generation of waste and the occurrence of holidays or festivals. Consequently, an analysis of waste-to-energy projects will facilitate the transformation of waste into electricity, thereby creating additional space in temples and promoting the utilization of environmentally friendly energy sources.